1991
DOI: 10.1002/hep.1840140620
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of acute fascioliasis with bithionol

Abstract: Fascioliasis is the parasitic infestation of the liver and biliary tract related to Fasciola hepatica. Bithionol is proposed as the treatment of choice for human fascioliasis without major side effects. However, the efficacy of bithionol has been evaluated in chronic but not in acute fascioliasis. In this study we report on the success of treatment with bithionol in 10 patients with fascioliasis, 8 having acute fascioliasis. The criteria for the diagnosis of fascioliasis were hypereosinophilia, positive immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 17 publications
(17 reference statements)
0
18
0
Order By: Relevance
“…In fact, these compounds may be of use for the veterinary treatment of Avian Polyomavirus, which can cause acute death in a wide range of psittacine birds (Katoh et al, 2010). Further, in geographical regions where fluke outbreaks in humans are more problematic, bithionol has been used to successfully clear infections in humans after oral administration (Bacq et al, 1991; Kim, 1970; Lee and Kim, 2006; Price et al, 1993; Seo et al, 1982). …”
Section: Discussionmentioning
confidence: 99%
“…In fact, these compounds may be of use for the veterinary treatment of Avian Polyomavirus, which can cause acute death in a wide range of psittacine birds (Katoh et al, 2010). Further, in geographical regions where fluke outbreaks in humans are more problematic, bithionol has been used to successfully clear infections in humans after oral administration (Bacq et al, 1991; Kim, 1970; Lee and Kim, 2006; Price et al, 1993; Seo et al, 1982). …”
Section: Discussionmentioning
confidence: 99%
“…These studies also point the way to in vivo studies, as one of the lead compounds (bithionol) has received Food and Drug Administration approval as a second-line orally administered medication for the treatment of helminthic infection that can be safely dosed in humans at 25 mg kg À1 body weight per day (46). Detailed toxicology and pharmacokinetics on the drug are available, and oral doses of 50 mg/kg in three divided alternate daily doses for 5 days maintain serum levels in the range of 140 to 550 Amol/L in rabbits, dogs, and humans, or several times greater than those required to observe a 50% inhibition of melanoma cell migration in our in vitro assays.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we investigated the novel combination of cisplatin with Bithionol [2, 2′-Sulfanediylbis (4, 6-dichlorophenol)] (BT) as an alternate therapeutic strategy. BT is a Food and Drug Administration-approved antiparasitic agent that has been safely dosed in humans to be used orally as a second-line medication for the treatment of helminthic infections [25]. Previously, we showed that BT exerts cytotoxic effects on a panel of ovarian cancer cell lines regardless of their cisplatin sensitivities [26].…”
Section: Introductionmentioning
confidence: 99%